Evaluasi Tata Kelola Teknologi Informasi pada PT. Aerofood Indonesia Bandar Udara Soekarno Hatta Cengkareng dengan Menggunakan Framework COBIT Versi 5.0 - Joshua Soejanto; Suprapto Suprapto; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Aerofood Indonesia was company that had been appointed together with the command of State-Owned Enterprises namely PT. Garuda Indonesia, Tbk. PT. Aerofood Indonesia is a company focused in in-flight services catering services. In the daily operational activities PT. Aerofood Indonesia uses information technology as a source of support in business activities to support infrastructure and communication services in-flight catering services. With implemented of information technology at PT. Aerofood Indonesia there were problems that often occured in corporate information technology services. This problem would required a solution. For that company they need a process that is focused in the problems appear in the company PT. Aerofood Indonesia. This problem refered to the existing DSS domain in the framework COBIT version 5. Need an evaluation process to be able to help to provided information and recommendations that are beneficial to the company in order to overcome the problems in the IT company PT. Aerofood Indonesia. The evaluation process is based on COBIT method that is Process Assessment Model. From the results of the evaluation the company is getting the (as-is) value for the subdomain DSS01 is at level 3, and the (as-is) value for the subdomain DSS02 is at level 2, while the (as-is) value for subdomain DSS03 is at level 2. Within the assessment process founded the gap based on the value of the expected capability (to-be) of 1.0 point. In this case the existing IT department at the company want expectations that can be achieved at one level above level (as-is). With this evaluation is expected to help companies to improve strategic decisions.